2021
DOI: 10.3390/su13052676
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Analysis on Gender Aspects in Transport Systems and Mobility Services: Presentation of a Survey Design

Abstract: As sustainability is becoming a common practice in planning transport systems and mobility services, the designation and management of gender issues are of paramount importance. TInnGO is a European Project that has developed a network of 10 national Hubs to build the capacity to generate and apply evidence on gender equality and transport issues at the European level. This paper presents the project activities by introducing a relevant framework and exploring user mobility experiences based on gender to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 35 publications
2
27
1
Order By: Relevance
“…Women were less attracted to MaaS in general (GENDER_F), but they seemed to appreciate bundles containing unlimited urban transportation services (GENDER_FxTPL). is is somewhat consistent with recent studies reporting that women do not well receive shared mobility regarding safety, reliability, and user-friendliness, even though women are known to use public transportation more than men do [42]. is also highlights the need for additional studies on the gender gap in the transportation sector [43].…”
Section: Maas Adoption-model Estimationsupporting
confidence: 84%
“…Women were less attracted to MaaS in general (GENDER_F), but they seemed to appreciate bundles containing unlimited urban transportation services (GENDER_FxTPL). is is somewhat consistent with recent studies reporting that women do not well receive shared mobility regarding safety, reliability, and user-friendliness, even though women are known to use public transportation more than men do [42]. is also highlights the need for additional studies on the gender gap in the transportation sector [43].…”
Section: Maas Adoption-model Estimationsupporting
confidence: 84%
“…Recent results suggest that safety, security, accessibility, and transport reliability are the main issues related to women's mobility [34]. Given these gender differences in transport, there is a need to focus on women's transport issues and undertake further research on the mobility needs of women to provide the evidence base for inclusive transport policies [35].…”
Section: Women's Mobility and Travel Behaviourmentioning
confidence: 99%
“…Previous studies have shown that different user characteristics, including social roles rooted in society, lead to different activity patterns and a gender mobility gap. Women are known to use Public Transport (PT) more than men, who in a traditional society make commuting trips by car and get the first right to car usage in a household [8]. However, during the pandemic, governments and local authorities implemented restriction measures to reduce the use of PT, as their overcrowding represents a highlevel risk of contagion [9].…”
Section: Women's Mobility Habits and Covid-19 Emergencymentioning
confidence: 99%